The Effectiveness of Life Skills Training in Male Students’ Anger Control - Eshrat Takrousta (Journal of Global Pharma Technology, 2017)
This study aims to determine the effect of life skills training to primary sixth-grade students of 18 region of Tehran education. This is a semi-experimental research with pretest-posttest design and control group. The statistical population includes the primary sixth-grade students of region 18 of Tehran education who were sampled using multi steps random sampling method.  Aggression questionnaire of Nelson et al (2000) is used to collect data. The research hypotheses regarding the effect of life skills training (emotional management) to students on their anger control is examined by univariate analysis of covariance (ANCOVA). Results of the test show that anger life skills training to students is effective in controlling primary sixth-grade male students’ anger and 57.5% of subjects’ anger control variance is explained by the independent variable, i.e., life skills training. Moreover, multivariate unilateral intergroup covariance analysis (MANCOVA) is used to measure the effect of life skills training on anger control components of the participants. The results reveal that the average score of students in failure, physical aggression, relationships with peers and relations with authorities is simultaneously different between the members of the control and life skills training groups.Keywords: Life skills, Anger, Students.